Promoting genre-based methodology in Algerian ESP classes: Teachers’ attitudes and current practices - Mahbouba MESSERHI (Langues & Cultures)
Genre analysis is an effective way for presenting specialized language in ESP classes; however, limited research was conducted on its implementations in Algerian universities. Drawing on teachers’ perspectives, this study aimed to elicit Algerian ESP practitioners’ cognition of genre analysis and its relevance to ESP instructions, as well as to explore their’ current practices to support learners’ genre awareness. Data obtained through an online questionnaire revealed that while the respondents recognized the alignment of genre-based instructions with the goals of ESP teaching, they admitted that this methodology is not regularly included in their classes. The paper suggests advocating a more discourse-oriented methodology to teaching ESP in Algerian universities rather than focusing on merely linguistic competence in a decontextualized way.